2018
DOI: 10.1002/anie.201801573
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Dehydrogenative Alkylation or α‐Olefination of Alkyl‐Substituted N‐Heteroarenes with Alcohols

Abstract: Catalysis with earth-abundant transition metals is an option to help save our rare noble-metal resources and is especially interesting when novel reactivity or selectivity patterns are observed. We report here on a novel reaction, namely the dehydrogenative alkylation or α-olefination of alkyl-substituted N-heteroarenes with alcohols. Manganese complexes developed in our laboratory catalyze the reaction with high efficiency whereas iron and cobalt complexes stabilized by the same ligands are essentially inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 70 publications
0
61
0
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][60][61][62][63] Metal-ligand cooperative catalysis [64][65][66][67] can dramatically improve catalytic performance of ADC reactions using pincer ligands bearing NH, OH or CH 2 functionality. [40][41][42][43][44][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Milstein, [40] Sun, [41] Yu, [42] Kundu [43] and Chen [44] have independently developed bifunctional Ru(II) catalysts for the synthesis of pyridine and quinoline derivatives (Scheme 1), but these catalysts were often air/water sensitive, involved a somewhat complicated synthesis, or required to...…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][60][61][62][63] Metal-ligand cooperative catalysis [64][65][66][67] can dramatically improve catalytic performance of ADC reactions using pincer ligands bearing NH, OH or CH 2 functionality. [40][41][42][43][44][68][69][70][71][72][73][74][75][76][77][78][79][80][81] Milstein, [40] Sun, [41] Yu, [42] Kundu [43] and Chen [44] have independently developed bifunctional Ru(II) catalysts for the synthesis of pyridine and quinoline derivatives (Scheme 1), but these catalysts were often air/water sensitive, involved a somewhat complicated synthesis, or required to...…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the Maji et al and the Kempe's group independently reported manganese-catalyzed olefination of alkyl-substituted N-heteroarenes 12 with alcohols 1. While Kempe and coworkers approached the reaction with the PNPÀ Mn complex Mn-22 (Scheme 12a), [30] Maji et al used an in situ generated NNN-pincer stabilized complex Mn-23 for the ADC of Nheteroarenes 12 with 1 (Scheme 12b). [31] In both cases, it was found that the reaction was highly selective and gave only Zisomer of the olefination product 13.…”
Section: Olefination Of N-heteroarenesmentioning
confidence: 99%
“…Remarkably, water and hydrogen were eliminated as the byproducts, making this reaction fairly environmentally benign. At the same time, such an olefination reaction was also developed by Kempe's group, using a manganese catalyst supported by a PNP pincer ligand . A possible reaction mechanism was proposed after careful mechanistic studies (Scheme ).…”
Section: Olefination Reactions With Alcoholsmentioning
confidence: 99%
“…At the same time, such an olefination reaction was also developed by Kempe's group, using a manganese catalyst supported by a PNP pincer ligand. [33] A possible reaction mechanism was proposed after careful mechanistic studies (Scheme 12). Initially, the real catalytic active manganese species Mn-8 was generated upon preactivation with a base.…”
Section: Olefination Reactions With Alcoholsmentioning
confidence: 99%